Flood Damages in an Infrastructure Climate Risk Stress Test: A Case Study of a Solar Power Plant Project - Pasha, Muhammad Dafa Sultan; Dirgantara, Gan Gan; Wiliandi, Sandi Krisna; Budianto, Endi Trimawan (Journal of Infrastructure Policy and Management, 2025)
Climate change presents significant risks not only to the environment but also to financial systems. In response, climate risk stress testing (CRST) has become an important tool for regulators and financial institutions. However, most applications of CRST to date have focused on real estate and mortgage exposures, with little attention given to infrastructure assets. This paper addresses that gap by exploring methodologies to analyze flood-related physical risk for infrastructure in the context of CRST. The study applies the hazard–vulnerability–exposure approach by combining global flood hazard data from the Aqueduct tools, depth-damage functions, and simplified assumptions on asset exposure. A case study on an anonymized solar power plant project in Indonesia is conducted to demonstrate the methodology. The analysis produces estimates of financial loss using both single-event damage and Expected Annual Damage (EAD), which can then be integrated into project-level financial stress tests. The results show that this framework provides a practical and transparent way to quantify climate-induced flood risk for infrastructure, offering a starting point for regulators, development finance institutions, and multilateral development banks. At the same time, several weaknesses are identified, including the coarse resolution of global hazard maps, generic vulnerability functions are not calibrated for local conditions, and the absence of considerations for flood protection and indirect financial impacts.